Structural characterization of an α-1, 6-linked galactomannan from natural Cordyceps sinensis. (May 2018) - Wang, Junqiao; Nie, Shaoping; Chen, Shuping; Phillips, Aled O.; Phillips, Glyn O.; Li, Yajing; Xie, Mingyong; Cui, Steve W.
Abstract: An α-1, 6-linked galactomannan was isolated and purified from natural Cordyceps sinensis . The fine structure analysis of this polysaccharide was elucidated based on partial acid hydrolysis, monosaccharide composition, methylation and 1D/2D nuclear magnetic resonance (NMR) spectroscopy. Monosaccharide composition analysis revealed that this polysaccharide was mainly composed of galactose (68.65%), glucose (6.65%) and mannose (24.02%). However, after partial acid hydrolysis the percentages of galactose, glucose and mannose were changed to 3.96%, 13.82% and 82.22%, respectively. The molecular weight of this polysaccharide was 7207. Methylation and NMR analysis revealed that this galactomannan had a highly branched structure, mainly consisted of a mannan skeleton and galactofuranosyl chains. The structure of galactofuranosyl part was formed by alternating (1 → 5)-lined β-Gal f and (1 → 6)-liked β-Gal f or a single (1 → 6)-liked β-Gal f, attaching to the O -2 and O -4 of the mannose chain, and terminated at β-T-Gal f . The mannan core was revealed by analyzing the partial acid hydrolysate of the galactomannan and the structure was composed of (1 → 6)-linked α-Man p backbone, with substituted at C-2 by short chains of 2-substituted Man p or Gal f branches. Graphical abstract: Image 1 Highlights: New polysaccharides from natural Cordyceps. Detailed structural characterization. Provide guidance for fermented Cordyceps products.